THE NECESSITY OF THE INFLUENCE OF LONGITUDINAL FORCES ACCOUNTING, ARISING IN THE DOUBLE-HINGED CONCRETE ARCH DURING THE POWER IMPACTS - Tatarinov, O. F. (Science and Transport Progress, 2007)
The basis of calculation of flexibility of steel-concrete building elements is offered on the example of archs of continual cross-section. The numerical calculations, confirming the necessity of calculation of flexibility characteristics while calculating elements of small cross-section.